Uguali e diversi. Interviste a migranti - Saba, Riccardo; Telesforo, Ludovica; Tulli, Federico (Il sogno della farfalla, 2018)
Comprehensive understanding of the impact migration can have on mental health should first of all consider the points of view of those who experience it firsthand: migrants. Hence, four interviews with four different people, who faced and came to know a faraway world that was unknown to them, have been reported here. An adolescent, a woman, and two men, coming from different continents, and driven by their need to survive or personal requirements, tell readers about their opinions on equality, travelling and integration, highlighting how difficulties can turn into opportunities, and how these may lead to achieving a new human identity.